2008
DOI: 10.1016/j.jada.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Water Consumption Reduces Energy Intake at a Breakfast Meal in Obese Older Adults

Abstract: Water consumed before a meal has been found to reduce energy intake among nonobese older adults. However, it is unknown whether this effect is evident among overweight and obese older adults, a population who would benefit from strategies to improve energy intake regulation. Our purpose was to determine whether premeal water consumption reduces meal energy intake in overweight and obese older adults. Twenty-four overweight and obese adults (body mass index=34.3±1.2), mean age 61.3±1.1 years, were given an ad l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 22 publications
1
83
2
6
Order By: Relevance
“…A number of previous studies have investigated the effect of pre-meal water ingestion on ad-libitum energy intake at a single meal [7][8][9], with water ingested either 30 min or 60 min before the ad-libitum meal. Studies of obese [9] and non-obese [8] older adults (~60 y of age) have reported that a water preload ingested 30 minutes before a meal, reduces ad-libitum energy intake at the meal compared to a no preload trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of previous studies have investigated the effect of pre-meal water ingestion on ad-libitum energy intake at a single meal [7][8][9], with water ingested either 30 min or 60 min before the ad-libitum meal. Studies of obese [9] and non-obese [8] older adults (~60 y of age) have reported that a water preload ingested 30 minutes before a meal, reduces ad-libitum energy intake at the meal compared to a no preload trial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of obese [9] and non-obese [8] older adults (~60 y of age) have reported that a water preload ingested 30 minutes before a meal, reduces ad-libitum energy intake at the meal compared to a no preload trial. In contrast, studies of young adults have observed no effect on ad-libitum energy intake compared to a no preload control trial when water preloads are provided 30 minutes before a meal [7,8], 60 minutes before a meal [7] or during a meal [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental designs where sugar-sweetened beverages (SSB) have been replaced with water have yielded controversial findings (3)(4)(5)(6)(7) . Systematic reviews, primarily of observational studies, compared the effects of drinking water and other beverages on energy intake and concluded that water plays an important role in reducing energy intake (8,9) .…”
mentioning
confidence: 99%